2008
DOI: 10.1080/10739680801949732
|View full text |Cite
|
Sign up to set email alerts
|

The Atypical Zeta (ζ) Isoform of Protein Kinase C Regulates CD11b/CD18 Activation in Human Neutrophils

Abstract: These data suggest that PKCzeta is a negative regulator of Mac-1 affinity and a positive regulator of Mac-1 avidity. Further, Mac-1 avidity is more important than increased affinity alone in regulating neutrophil firm adhesion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…LFA-1 clustering induced by the chemokine CCL-21 was markedly reduced by a PKC-f pseudosubstrate inhibitory peptide (Giagulli et al 2004). For neutrophils, a similar approach was used by Chakrabarti and Patel (2008), who examined IL-8-induced Mac-1 clustering with or without the same PKC-f inhibitory peptide. By blocking PKC-f with that method, Mac-1 clustering was prevented (Chakrabarti and Patel 2008).…”
Section: Adhesion Strengthening and Crawlingmentioning
confidence: 99%
See 1 more Smart Citation
“…LFA-1 clustering induced by the chemokine CCL-21 was markedly reduced by a PKC-f pseudosubstrate inhibitory peptide (Giagulli et al 2004). For neutrophils, a similar approach was used by Chakrabarti and Patel (2008), who examined IL-8-induced Mac-1 clustering with or without the same PKC-f inhibitory peptide. By blocking PKC-f with that method, Mac-1 clustering was prevented (Chakrabarti and Patel 2008).…”
Section: Adhesion Strengthening and Crawlingmentioning
confidence: 99%
“…For neutrophils, a similar approach was used by Chakrabarti and Patel (2008), who examined IL-8-induced Mac-1 clustering with or without the same PKC-f inhibitory peptide. By blocking PKC-f with that method, Mac-1 clustering was prevented (Chakrabarti and Patel 2008). These findings suggest the involvement of PKC isoforms in outside-in signaling, because clustering of b 2 -integrins in neutrophils is mediated via outside-in signaling involving Src family kinases (Mócsai et al 1999(Mócsai et al , 2006Piccardoni et al 2004).…”
Section: Adhesion Strengthening and Crawlingmentioning
confidence: 99%
“…Once adherent, the ligand-bound integrins initiate outside-in signaling events that involve SYK (10) and Src kinases (11,12). Using pseudosubstrate inhibition, the atypical isoform protein kinase C (PKC)-z has been implicated in outside-in signaling downstream of the b 2 integrin Mac-1 (13), but Mac-1 has no known role in neutrophil adhesion under flow. The functional role of PKC has not yet been investigated in the context of neutrophil adhesion to the vascular endothelium (14).…”
mentioning
confidence: 99%
“…Several studies have shown that treatment of isolated human neutrophils with ζ-PKC pseudosubstrate inhibitor peptide significantly attenuates IL-8 induced adhesion [27]. Specifically, results from Chakrabarti et al point to a roll for ζ-PKC in the regulation of the β2-integrin CD11b (also known as MAC-1) affinity and avidity [74]. We take great interest in the finding that ζ-PKC attenuates IL-8 mediated neutrophil chemotaxis in vitro with no apparent effect on MARCKS phosphorylation and plan to perform follow up investigations.…”
Section: Discussionmentioning
confidence: 99%